Ports and their influence on local air pollution and public health: A global analysis - César Ducruet; Bárbara Polo Martin; Mame Astou Sene; Mariantonia Lo Prete; Ling Sun; Hidekazu Itoh; Yoann Pigné (Science of The Total Environment, 2024)

OME-Zarr: a cloud-optimized bioimaging file format with international community support - Josh Moore; Daniela Basurto-Lozada; Sébastien Besson; John Bogovic; Jordão Bragantini; Eva M. Brown; Jean-Marie Burel; Xavier Casas Moreno; Gustavo de Medeiros; Erin E. Diel; David Gault; Satrajit S. Ghosh; et al. (Histochemistry and Cell Biology, 2023)
A growing community is constructing a next-generation file format (NGFF) for bioimaging to overcome problems of scalability and heterogeneity. Organized by the Open Microscopy Environment (OME), individuals and institutes across diverse modalities facing these problems have designed a format specification process (OME-NGFF) to address these needs. This paper brings together a wide range of those community members to describe the cloud-optimized format itself—OME-Zarr—along with tools and data resources available today to increase FAIR access and remove barriers in the scientific process. The current momentum offers an opportunity to unify a key component of the bioimaging domain—the file format that underlies so many personal, institutional, and global data management and analysis tasks.